The Construction of Corporate Fault related to Corporate Criminal Liability in the New Criminal Code: Implications and Formulation - Sanathana Ishwara, Ade Sathya (IHSA Institute, 2024)
On January 6, 2023, President Joko Widodo signed a new Penal Code (Law No. 1/2023) regulating corporate criminal liability in Indonesia, introducing significant changes in corporate criminal law. This regulation alters the definition, subjects, conditions of liability, justifications, and sanctions for corporations. The aim of this research is to identify the implications of the construction of corporate fault in the new Penal Code on corporate criminal liability in Indonesia and to formulate appropriate criminal sanctions based on this construction. The research employs a normative legal method with a legislative approach to analyze the construction of corporate fault in Law No. 1/2023, affecting corporate criminal liability in Indonesia. Data is gathered from legal texts, court decisions, legal literature, and analyzed with a focus on the implications and formulation of suitable sanctions for corporations. The implications of the construction of corporate fault in the new Penal Code (Law No. 1/2023) on corporate criminal liability in Indonesia are highly significant, expanding the accountability of corporations and individuals involved in corporate criminal activities. Despite varying opinions on these changes, the implementation of the new Penal Code reflects the government's commitment to improving corporate governance, promoting legal compliance, and ensuring the protection of public interests. The formulation of appropriate and proportionate criminal sanctions should encompass various aspects, ranging from fines to rigorous monitoring, restitution, and corporate education, to foster a more ethical and sustainable business environment while maintaining fairness and legal certainty.